Data Without Meaning: Establishing the Significant Properties of Digital Research - Gareth Knight; Maureen Pennock (International Journal of Digital Curation, 2009)
It is well recognised that the period of time in which digital research may remain accessible is likely to be short in comparison to the period in which it will continue to hold intellectual value. Although many digital preservation strategies are effective for simple resources, it is not always possible to confirm that all of the significant properties - the characteristics that contribute to the intended meaning - have been maintained when stored in different formats and software environments. The paper outlines methodologies being developed by InterPARES, PLANETS and other projects in the international research community to support the decision-making process and highlights the work of four recent JISC-funded studies to specify the significant properties of vector images, moving images, software and learning objects.